Can quantitative 18F-FDG PET/CT and serum cytokine analysis differentiate ARVC from cardiac sarcoidosis?. (25th November 2020) - Abbas, H; McKiddie, F; Kouri, M; Duncan, L; Fong, M; Wilson, E; Norris, K; Matheson, J; Scally, C; Dempsey, O; Denison, A; Wilson, H.M; et al.
Abstract: Background: Arrhythmogenic right ventricular cardiomyopathy (ARVC) and Cardiac Sarcoidosis (CS) may both cause malignant arrhythmia and sudden death, but differentiating the two can be difficult. Purpose: To investigate the role of quantitative FDG PET/CT at distinguishing ARVC from CS, and explore whether addition of an inflammatory panel correlates with PET uptake, aiding diagnosis. Methods: 10 patients with CS, 10 with ARVC were enrolled. Participants were prospectively studied with PET/CT. LV uptake was quantified using software and a 17-segment model, measuring maximum standardised uptake (SUVmax) and mean myocardial uptake, comparing these to a local normal reference range (21 volunteers) using a z-score. Blood levels of IL-1b, IL-6, IL-8, IL10, IL-12p40, MCP-1, TGFb, GRO, TNFa, IFNy, FGF2, PDGF were measured using ELISA, compared with 10 healthy controls. Results: There were no significant differences in cytokine levels between CS and ARVC; most cytokine levels were higher in CS, except IL-6, IL-8 and MCP-1 in ARVC (Table 1). Increased PET uptake was noted in 1 segment of 1 ARVC patient, and in 1–2 segments of 5 CS patients (z-scores 2.25 SD; 2.15–2.38 SD). No pattern of uptake distinguished ARVC from CS, qualitatively assessing LV polar maps (Figure 1A, B). SUVmax and mean uptake were higher in CS vs. ARVC (p<0.05; p=0.13). No significant correlation between cytokine levels and PET uptake was detected (Figure 1C, D). Conclusion: Quantitative PET/CT uptake and a blood inflammatory panel did not have utility in differentiating the two conditions in our population. There was generally more PET and serum inflammatory activity in CS. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): NHS Endowments